Anticancer and Antioxidant activity of Tephrosia calophylla against cancer cell lines - Ramesh C; Prameela Rani (International Journal of Phytomedicine, 2019)
To evaluate anticancer and antioxidant potentials of activity of methanol extract of Tephrosia calophylla. The methanol extract of Tephrosia calophylla was prepared and tested for in vitro anticancer activity by using human MCF 7, HCT-116, HEP-G2, A-549 cancer and vero normal cell lines. The antioxidant activity for the extract was evaluated by Superoxide scavenging, Lipid peroxidation and DPPH methods. IC50 values of extracts were parameters in both studies. The results of the study have shown that methanol extract of Tephrosia calophylla has shown significant IC50 values against MCF 7, HCT-116 and A-549 cell lines which shows its anticancer potentials but inhibitory effect of methanol extract against HEP-G2 and vero cell lines was not significant. The results also suggest that the methanol extract of Tephrosia calophylla has significant antioxidant properties against Superoxide scavenging, Lipid peroxidation and DPPH methods. The present study shows anticancer potentials of methanol extract of Tephrosia calophylla against MCF 7, HCT-116 and A-549 cell lines.